Pengaruh Brand Identity, Motivasi Terhadap Keputusan Menginap Dengan Religiusitas Sebagai Variabel Moderasi Pada Hotel Syariah - Padyan Farhaani Yadhaningrum; Lukluk Atul Hidayati (Borobudur Management Review, 2021)
This,study aims to determine the effect of brand identity and motivation with religiosity as a moderating variable on,thedecision to stay,at a sharia hotel. This study was conducted looking at the phenomenon of gap and gap research, which shows inconsistencies resulting from previous studies. The population of this study amounted to 100 respondents who are people who have stayed at sharia hotels. Samples were taken using the quota sampling method as a determinant of the number of respondents who had stayed at sharia hotels. The sample taken is people who have stayed at sharia hotels. The data in this study are primary data, namely data obtained by distributing questionnaires through google form. The questionnaires obtained were 100 and processed were 100 questionnaires. The method used in data analysis is Moderate Analysis Regression (MRA). The results of the study stated that the brand identity and motivation variables had a positive and significant effect on the decision to stay. After being moderated by religiosity, the brand identity variable has no effect on the decision to stay. Likewise, religiosity cannot moderate the influence,of motivation on the decision to stay. This research is not perfect, there are still limitations faced by the author, such as; The scale of this study is still small, the results of the data are still subjective because there is no deepening, and also the limitations of reference sources.